Innovative Services During Pandemic at UIN Sunan Kalijaga Yogyakarta Library: A ServQual Analysis - Marwiyah; Labibah; Khotimah, Khusnul; Astuti, Sri; Prabowo, Thoriq Tri (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
Academic library contributes much to the realization of the three pillars of higher education, which are education, research, and social services. During pandemic, university library has to keep contributing to the development of education even when learning-teaching activities are virtually conducted. This research is aimed at identifying sorts of service developed by UIN Sunan Kalijaga Yogyakarta library during the pandemic and at exploring the users’ responses to them by using ServQual approach to evaluate three aspects of innovative services, namely the services being developed, the service supporting facility, and the human resources. This research uses a qualitative method. The data were collected through interviews with 17 qualified informants and documentation. The study showed that the library has made some innovative services to satisfy the users’ needs, particularly the students who were doing their last assignments. The users have benefited much from the innovative services and declared their satisfaction. In term of facility, the library is completed with facilities and infrastructure that are in line with the health protocols. The library also used social media, like WhatsApp and Instagram, to support its services. In addition, the librarians have significantly helped the users access the services.